THE PROBLEM OF BORROWING WORDS IN THE FIELD OF SPORT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Sports are of interest even to those who have traditionally tended to be just a casual spectator. Sport becomes a necessary part of our lifestyle under the impact of  mass culture and clothing. Sport words go far beyond definition of theoretical or technical expertise relevant only to a given industry. They are gradually connected  with the idea of “healthy lifestyle” in the context of modern knowledge about an individual. Possession of sporting language and jargon is one of the prerequisites of improving a native speaker’s communication skills. The  objectof the article seems important  to us in this regard.  The purpose of the research is to examine the composition and definition of the sport-related  terminology, words,phraseological  units that function in modern linguistics. In the research, analysis techniques, definition, generalization, systematization and numerical approach have been used. We identified: sport words, word blends, terminology from various fields of knowledge (used as sports), neologisms, professionalism  and formal vocabulary, tracking articles and metaphors in the course of studying  journalistic text  on sport topics. Another outcome of the analysis of sport terminology was the grouping of chosen units in keeping with the source language. Terms are the foundation of sport terminology. Based on the research,we found that in the texts from newspapers  and internet sources of sports subjects borrowings in a language.